Reverse logistics by food retailers in Klang Valley, Malaysia - Vijayan, Gowri; Kamarulzaman, Nitty Hirawaty; Mohamed, Zainal Abidin; Abdullah, Amin Mahir (Management Science Department, Bahria University Karachi Campus, 2014)
Perishability of products is one of the most important challenges faced by food supply chains worldwide. The delicate nature of its business thereby stress on smooth movement of the forward supply chain. This does not, however prevent the backward movement of food materials. The backward management of these materials requires adoption of efficient reverse logistics practices. Although reverse logistics is widely studied across industries by researchers, information on reverse logistics in the Malaysian food retail industry is limited. The limited number of studies conducted on recent developments in the industry and reverse logistics indicate a major gap in sustainability logistics studies. Considering the importance given to green movement by the government of Malaysia, it is necessary to understand this sustainable logistics process. This study aims to investigate reverse logistics adoption by retailers in Klang Valley, Malaysia. Klang Valley had been selected as area of study due to its high retail format population, which supports multi-format retail study including grocery stores, convenience stores, supermarkets, and hypermarkets. The results highlight benefits perceived by retailers from reverse logistics and barriers to adopt reverse logistics. Consumers’ unconcern towards greening of retail store operations act as a major inhibitor to adoption of reverse practices by retailers. This study could be used as a precursor for further detailed studies on this issue.